The new-look of PubMed: A brief description of the changes in PubMed - Fabio Frisone; Rosaria Micali (Mediterranean Journal of Clinical Psychology, 2020)
The advancement of technology has made it possible to obtain discrete results in terms of scientific information.  Among the many innovations made recently, there is the possibility of accessing the changes and improvements offered by the new updated PubMed.  This brief description aims at highlighting the main innovations operated by PubMed to make the field of scientific information more practical and reachable by everyone.